2019
DOI: 10.1001/jamanetworkopen.2019.1340
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Risk Evaluation and Mitigation Strategy Program With Transmucosal Fentanyl Prescribing

Abstract: Key Points Question Was the implementation of the Transmucosal Immediate-Release Fentanyl (TIRF)–Risk Evaluation and Mitigation Strategy (REMS) associated with changes in prescribing of TIRF medications? Findings In this cohort study using interrupted times series analysis, implementation of TIRF-REMS was associated with a temporary reduction in the rate of overall TIRF prescribing to Medicare Part D beneficiaries and with a sustained decrease in the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Our study confirms previous findings that IRF prescribing is low in European countries [ 24 , 25 ]. After all, IRF should be reserved as a last resort for breakthrough pain in cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirms previous findings that IRF prescribing is low in European countries [ 24 , 25 ]. After all, IRF should be reserved as a last resort for breakthrough pain in cancer.…”
Section: Discussionsupporting
confidence: 92%
“…A United States FDA Risk Evaluation and Mitigation Strategy (REMS) program was also implemented to assess transmucosal immediate-release fentanyls (TIRFs) and found that substantial rates of TIRFs were prescribed inappropriately 145,146 . With the findings of deficiencies in the structure and administration of TIRFs, the development of other REMSs is needed to ensure the safe and appropriate use of approved drugs, especially dangerous opioid drugs 147 .…”
Section: Interventions For the Management And Prevention Of Fentanyl mentioning
confidence: 99%
“…8 However, few analyses of REMS programs with ETASU provide insight into patient experiences and perceptions. [9][10][11] A study by the manufacturer of the teratogenic multiple myeloma drugs lenalidomide and thalidomide found a high rate of self-reported adherence with birth control requirements (96%) and comprehension of teratogenic risk (98%). 12 Another investigation reported that while 89% of patient educational materials from 23 REMS programs met the criteria for being understandable, only 49% were deemed actionable, resulting in the reader knowing how to act on the messages being communicated.…”
Section: Introductionmentioning
confidence: 99%